2016
DOI: 10.1002/2015ja021698
|View full text |Cite
|
Sign up to set email alerts
|

Initial deflection of middle‐latitude Pi2 pulsations in the premidnight sector: Remote detection of oscillatory upward field‐aligned current at substorm onset

Abstract: In this study, we examined middle‐ and low‐latitude Pi2 events to address the following two issues regarding the well‐known substorm current wedge (SCW) model for Pi2 pulsations: (1) the center of the SCW, which is estimated using the Pi2 polarization pattern, is not always collocated with that determined using the magnetic bay pattern; and (2) although ideally Pi2 hodograms would be linear, they tend to become circular. In this study, auroral breakup events were identified from Polar Ultraviolet Imager data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…The middle-latitude Pi 2 pulsation in the D component detected the perturbation of the earthward portion of the upward and downward FACs in the SCW system. A major difference between T19 and our study is that T19 applied the oscillating FAC model proposed by Lester et al (1983) and Imajo et al (2015), but our study based on the oscillating FAC model developed by the successive study of Uozumi et al (2009Uozumi et al ( , 2011Uozumi et al ( , 2016 as introduced in section 1. Their observation confirmed that the presence of identical Pi 2 oscillations in the azimuthal components at topside ionosphere and ground.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The middle-latitude Pi 2 pulsation in the D component detected the perturbation of the earthward portion of the upward and downward FACs in the SCW system. A major difference between T19 and our study is that T19 applied the oscillating FAC model proposed by Lester et al (1983) and Imajo et al (2015), but our study based on the oscillating FAC model developed by the successive study of Uozumi et al (2009Uozumi et al ( , 2011Uozumi et al ( , 2016 as introduced in section 1. Their observation confirmed that the presence of identical Pi 2 oscillations in the azimuthal components at topside ionosphere and ground.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…Uozumi et al (2009) found that the H component of a high-latitude Pi 2 exhibits systematic group delays (|T| <~100 s) from the low-latitude Pi 2 in H. On the other hand, the delay time of the high-latitude Pi 2 in the D component to the low-latitude Pi 2 from the H component was not significant (|T|<~10 s) in the entire nighttime sector, and the high-latitude D component Pi 2s switched their polarity around 1 hr MLT dawnward of the auroral breakup center that was identified by global auroral image of the Polar satellite. Uozumi et al (2009Uozumi et al ( , 2011Uozumi et al ( , 2016 proposed a generation and propagation mechanism of global high-correlation Pi 2 event based on ground observations. Uozumi et al (2009Uozumi et al ( , 2011Uozumi et al ( , 2016 proposed a generation and propagation mechanism of global high-correlation Pi 2 event based on ground observations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Pi2 pulsations are a damped magnetic oscillation with a period of 40-150 s. They are observed at the onsets of substorms very often along with midlatitude positive bays. The spatial distributions of magnetic Journal of Geophysical Research: Space Physics 10.1002/2017JA024792 signatures suggest that the positive bays are the DC component of the substorm wedge current (e.g., Clauer & McPherron, 1974), whereas the Pi2's are its AC component (e.g., Lester et al, 1983;Uozumi et al, 2016). If the Pi2 pulsations are the manifestation of the damped oscillation of the substorm wedge current, it appears to be inconsistent with our conclusion that the M-I current circuit is overdamped.…”
Section: Pi2 Pulsationsmentioning
confidence: 99%